Etiologic Spectrum of Intestinal Obstruction in Ningxia District: A Retrospective Analysis of 4908 Cases in a 10-Year Period. (26th June 2019) - Jiang, Wei; Li, Wenyan; Hao, Qian; Yao, Yuping; Li, Yajun; Ge, Jun; Zhai, Huihong
Abstract : Background . Economic disparity contributes to the variation of intestinal obstruction (IO) etiologic spectrum. Clarifying the etiology distribution in local regions can help to unravel IO and promote early diagnosis, henceforth making sure standardized therapeutic interventions. Methods . Medical data of 4908 inpatients diagnosed with IO admitted to the General Hospital of Ningxia Medical University between January 2004 and December 2013 were recruited and analyzed retrospectively. The associated profiles included demographic features, clinical manifestations, and previous therapeutic operations. Results . 4908 cases of intestinal obstruction were identified during the period of study. It denoted that the hospitalization rate of IO has maintained upward momentum; the top four causes of IO were adhesion, tumor, intussusception, and hernias. These covered up nearly 80% of the total constitution. Among them, adhesive intestinal obstruction accounted for 45.17%, malignant bowel obstruction for 21.09%, intussusception for 8.72%, and hernia for 4.73%; abdominal surgery constituted for the majority (78.62%) of adhesive obstruction. The followed up analysis also found that appendectomy accounted for the biggest percentage, 28% of operation cases. Malignant bowel obstruction can have a rate of 96.43% in 1035 cases led by tumor lesions. Of which, the primary intestinal malignant tumor accounted for 68.64% and metastatic tumors for 31.36%. Nearly 50% occurred in the large intestine. The overall mortality of all 4908 cases was 4.7%. Conclusion . The hospitalizations of IO delineated an increasing trend. Adhesion was the main etiology in IO. The odds of malignant bowel obstruction was increasing in the proportion of IO. There were some differences towards the etiologic spectrum compared with western countries.